PERLINDUNGAN HUKUM KEWIRASWASTAAN DALAM BERINVESTASI DI PERUSAHAAN STARTUP - Bowoarota, Abram Pambudi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
As technology develops in this Industrial Revolution of 4.0,technology companies have gained the spotlight among other business sectors. Many business actors are competing to establish a company or known as a startup in the technology sector. Depart from the facts; the question arises: how is the condition of Indonesia to protect the entrepreneurship for startups? Through legal approach, this paper will explain current legal condition and legal structure of the Indonesian innovation system. The reason to review the law is to relate with the government’s target to create 1000 digital startups alike as in Silicon Valley level size. Therefore, legal framework review becomes useful to explain the condition of the law as a supporting system. In this sense, the legal prescription can be generated to confirm Indonesian Laws, Indonesian government categorizes the innovative industry as a creative industry. However, there is still no resolute concept to follow. Therefore, some of law adjustment is needed to support the government’s plan to pursue commercialized innovation.